New concepts: growth hormone, insulin-like growth factor-I and the kidney - Rabkin, Ralph; Schaefer, Franz (Growth hormone & IGF research, 2004)
Both growth hormone (GH) and IGF-1 have major effects on normal kidney growth, structure and function and participate in the pathogenesis of certain kidney diseases. Furthermore when the kidneys fail there are profound changes in the circulating GH-IGF-1 system and the renal and systemic responses to these hormones. In this brief review we address the advances that have been made in our understanding of the relationship between growth hormone GH and IGF-1 and the kidney in health and the systemic and local perturbations that occur in kidney disease and identify key unanswered questions.
Gesehen am 12.01.2021